Endoparasites in guanaco (Lama guanicoe). Review of the situation in Argentina and registries in the province of San Juan - Gonzalez-Rivas, Cynthia Jesica (2019)
This study compiles records of endoparasites species in guanacos (Lama guanicoe) from Argentina. A bibliographic review of scientific works published between 1967 and 2017 was conducted. In addition, new unpublished records of localities within the province of San Juan were incorporated. The endoparasite fauna was represented by the phylum Nematoda, Platyhelminthes and Aplicomplexa, with a total of 65 total entries, 26 species mentioned and 14 others that were only identified at the genus level. The nematodes were the most numerous, followed by the Aplicomplexa and to a lesser extent the pylum Platyhelminthes. This work mentions for the first time the presence of nematodes such as Nematodirus sp, Trichuris sp, coccidia E. macusaniensis, E. ivitaensis and Eimeria sp in wild guanacos from the province of San Juan. There were few records in the environment with small populations of guanacos from the Puna ecoregion.